Errratum: Weihai Li, Guoquan Wang, Wenliang Li & Dávid Murányi (2012) Review of Neoperla (Plecoptera: Perlidae) from Guangdong Province of China. Zootaxa, 3597, 15–24. - Li, Weihai; Wang, Guoquan; Li, Wenliang; Murányi, Dávid (Zootaxa, 2013)
(Erratum)